Variation in detainee risk assessment within police custody across England and Wales - Stoneman, Melanie-Jane (Policing and society, 2019)
Every time a person is booked into police custody in England and Wales, they are assessed for risk of harm to themselves or others. National guidance is provided on what questions should be asked as part of this process; however, each year there are still instances of serious adverse incidents, self-harm and deaths in custody. The purpose of this study is to look at the extent to which the national guidance is being followed and the extent to which the risk assessment process varies between police forces. A Freedom of Information request was sent to all 43 police forces in England and Wales asking for information on their risk assessment process. This data was then analysed alongside findings from police custody inspection visits conducted by Her Majesty's Inspectorate of Constabulary. This study provides evidence that the risk assessment process is not consistent across police forces in England and Wales. Not only does the process vary from the national guidance, the content and delivery differs considerably between police forces. The findings highlight a practical problem for police forces in ensuring that risk assessment processes are conducted to a consistent standard and reflect national guidance. The study is, to the authors’ knowledge, the first time that this data has been collated and compared.